The Effect of Preoperative Anemia on Postoperative Morbidity and Mortality in Patients Undergoing Thoracic Surgery - (:unkn) unknown (My University, 2020)
Objective: Anemia is common in patients undergoing thoracic surgery due to three main riskfactors including iron deficiency, chronic disease and iatrogenic factors, all of which can beprevented and treated. Our hypothesis was that the incidence of anemia may be higher thanexpected and associated with perioperative complications.Method: The data belonging to a total of 107 adult patients were included in the finalanalysis. We recorded demographic features, pre- and postoperative laboratory findings,comorbidities, blood transfusion rates, complications, mortality, type of surgery, rate ofre-exploration,and duration of hospital stay.Results: The incidence of anemia was 43.9%, being higher in men with 57.4 percent. Anemicpatients had a significantly prolonged hospital stay, higher rate of ICU hospitalizations, higherlevels of pre- and postoperative creatinine and lower levels of postoperative Hb, Htc andpreoperative INR (p<0.05).Conclusion: Even though the rate of mortality was not affected, anemia was associated witha higher rate of ICU admission and longer hospital stay. In order to reduce anemia-inducedperioperative complications, the treatment of preoperative anemia should be considered forthoracic surgery patients.

Amaç: Anemi, göğüs cerrahisi geçiren hastalarda demir eksikliği, kronik hastalık ve iyatrojenik olmak üzere üç ana risk faktörü nedeniyle sık görülmektedir ve bunların tümü önlenebilir_x000D_ ve tedavi edilebilirdir. Hipotezimiz anemi insidansının beklenenden yüksek olabileceği ve_x000D_ perioperatif komplikasyonlarla ilişkili olabileceği yönündeydi._x000D_ Yöntem: Toplam 107 yetişkin hastaya ait veriler nihai analize dâhil edildi. Demografik özellikler, ameliyat öncesi ve sonrası laboratuvar bulguları, komorbiditeler, kan transfüzyon oranları, komplikasyonlar, mortalite, cerrahi türü, re-eksplorasyon oranı, hastanede kalış süresi_x000D_ kaydedildi._x000D_ Bulgular: Anemi sıklığı % 43.9 iken, erkeklerde % 57.4 ile daha yüksekti. Anemik hastaların_x000D_ hastanede kalış süreleri anlamlı derecede uzun, YBÜ’ye yatış oranları daha yüksek, ameliyat_x000D_ öncesi ve sonrası kreatinin düzeyleri daha yüksek ve ameliyat sonrası Hb, Htc ve ameliyat öncesi INR düzeyleri daha düşüktü (p<0.05)._x000D_ Sonuç: Ölüm oranı etkilenmese de, anemi daha yüksek YBÜ’ye yatış oranı ve daha uzun_x000D_ hastanede kalış ile ilişkiliydi. Anemiye bağlı perioperatif komplikasyonları azaltmak için göğüs_x000D_ cerrahisi hastalarında preoperatif aneminin tedavi edilmesi düşünülmelidir.
Torasik Cerrahi Geçiren Hastalarda Preoperatif Aneminin Postoperatif Morbidite ve Mortaliteye Etkisi